Palliative Care Challenges of Patients With Progressive Bulbar Palsy: A Retrospective Case Series of 14 Patients - Bublitz, Sarah K.; Weck, Christiane; Egger-Rainer, Andrea; Lex, Katharina; Paal, Piret; Lorenzl, Stefan (Frontiers in Neurology, 2021)
Progressive Bulbar Palsy (PBP) is a form of motoneuron disease and is widely classified as a subtype of Amyotrophic Lateral Sclerosis (ALS) with a shorter time of survival and female predominance. In this retrospective case series of 14 patients with PBP, we focus on challenges in palliative care for this patient cohort, including symptom control, gastrostomy, non-invasive ventilation, and end-of-life phase. We show, that rapid physical decline at the end of life is associated with bronchopulmonary infection and excessive oral secretion leading to a high level of symptom burden. Early and regular advance care planning discussions with a focus on oral secretion management with patients and caregivers are crucial.